An Italian, multicenter, real-world, retrospective study of first-line pazopanib in unselected metastatic renal-cell carcinoma patients: the 'Pamerit' study. (20th November 2020) - Mosca, Alessandra; De Giorgi, Ugo; Procopio, Giuseppe; Basso, Umberto; Cartenì, Giacomo; Bersanelli, Melissa; Naglieri, Emanuele; Galli, Luca; Caffo, Orazio; Fornarini, Giuseppe; Boccardo, Francesco; Porta, Camillo
Abstract: Objective: Despite the current immunotherapy era, VEGFR inhibitors maintain effectiveness in metastatic renal cell cancer. Real-world data concerning pazopanib are limited. The aim of this study is to add information about efficacy and safety of pazopanib as first-line treatment in metastatic renal cell cancer patients not enrolled into clinical trials. Methods: Retrospective analysis (the PAMERIT study) of first-line pazopanib in real-world metastatic renal cell cancer patients among 39 Centers in Italy. Outcomes were progression-free survival, overall survival, objective response rate and treatment-related adverse events. Kaplan–Meier curves, log-rank test and multivariable Cox's models were used and adjusted for age, histology, previous renal surgery, International Metastatic RCC Database Consortium score and pazopanib initial dose. Results: Among 474 patients, 87.3% had clear cell metastatic renal cell cancer histology. Most of them (84.6%) had upfront renal surgery. Median progression-free survival and overall survival were 15.8 and 34.4 months, respectively, significantly correlating with International Metastatic RCC Database Consortium's good prognosis ( P < 0.001), ECOG PS 0 ( P < 0.001), age (<75 years, P = 0.005), surgery ( P < 0.001) and response to pazopanib ( P < 0.001). After 3 months of pazopanib, overall disease control rate have been observed in 76.6% patients. Among International Metastatic RCC Database Consortium's favorable group patients, 57/121 (47%) showed complete/partial response. No unexpected AEs emerged. Conclusions: In this real-world study, metastatic renal cell cancer patients treated with first-line pazopanib reached greater progression-free survival and overall survival than in pivotal studies and had high response rates when belonging to International Metastatic RCC Database Consortium's favorable group, without new toxicities. Pazopanib has been confirmed a valid first-line option for International Metastatic RCC Database Consortium's good prognosis metastatic renal cell cancer patients who cannot be submitted to immunotherapy. Abstract : The PAMERIT study retrospectively confirmed first-line pazopanibas active, efficacious, safe and cost-effective in the real-worldmRCC patients, particularly in IMDC good prognosis patients.